2014
DOI: 10.1002/2014gl061803
|View full text |Cite
|
Sign up to set email alerts
|

A rapid decrease of the hydrogen corona of Mars

Abstract: Mars is believed to have lost much of its surface water 3.5 billion years ago, but the amounts that escaped into space and remain frozen in the crust today are not well known. Hydrogen atoms in the extended martian atmosphere, some of which escape the planet's gravity, can be imaged through scattered solar UV radiation. Hubble Space Telescope (HST) images of the ultraviolet H Ly α emission now indicate that the coronal H density steadily decreased by a factor of roughly 40% over 4 weeks, a far greater variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
110
0
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(117 citation statements)
references
References 32 publications
5
110
0
2
Order By: Relevance
“…Clarke et al . [] used HST observations to derive exobase densities decreasing from 5 × 10 4 to 3.5 × 10 4 cm −3 for an exospheric temperature of 340 K for L S = 331–345 near solar minimum, a factor of 2 lower than our values for the same L S range in May 2015. Bhattacharyya et al .…”
Section: Derived Exospheric Hydrogen Distribution and Escape Ratesmentioning
confidence: 63%
See 1 more Smart Citation
“…Clarke et al . [] used HST observations to derive exobase densities decreasing from 5 × 10 4 to 3.5 × 10 4 cm −3 for an exospheric temperature of 340 K for L S = 331–345 near solar minimum, a factor of 2 lower than our values for the same L S range in May 2015. Bhattacharyya et al .…”
Section: Derived Exospheric Hydrogen Distribution and Escape Ratesmentioning
confidence: 63%
“…Recent observations have revealed a high degree of variability in the hydrogen exosphere [ Chaffin et al ., ; Clarke et al ., , ; Yamauchi et al ., ; Bhattacharyya et al ., ; Romanelli et al ., ; Rahmati et al ., ; Halekas et al ., ], with higher column densities typically observed near perihelion and lower densities near aphelion. However, many of these observations have incomplete temporal coverage, and uncertainties in data inversion make it challenging to translate observations of seasonal variability into quantitative estimates of escape flux.…”
Section: Introductionmentioning
confidence: 99%
“…In the course of constraining the H escape flux, observations of Mars by Hubble Space Telescope (HST) in October–November 2007 identified a 40% decrease in intensity of scattered solar Lyman α by Martian exospheric hydrogen in ~4 weeks [ Clarke et al , ]. This trend, also observed by Mars Express over several months yielded up to an order‐of‐magnitude change in hydrogen escape flux [ Chaffin et al , ].…”
Section: Introductionmentioning
confidence: 75%
“…Interestingly, observational evidence of a strong seasonal dependence in the hydrogen exosphere of Mars has been recently reported in Clarke et al [], Chaffin et al [], and Bhattacharyya et al [], based on Hubble Space Telescope and MEX scattered Lyman α brightness observations. In agreement with these observations, a large decrease in the median penetrating proton density [ Halekas et al , ] derived from MAVEN Solar Wind Ion Analyzer (SWIA) [ Halekas et al , ] measurements is observed during the MAVEN mission (lower density values for larger heliocentric distances) and also indicates a high level of seasonal variability in the Martian H exosphere.…”
Section: Discussionmentioning
confidence: 94%